The return of the dead - Antonio Cavicchia Scalamonti (Funes)
Some biographical hints that might help to understand the path I have taken in my research. I lost my father at the age of one year and I have lived for several years (those that are fundamental to my psychic development) symbiotically with my mother. Then when I was older she got remarried and had my brother. I was just over thirty years old when my mother died in a car accident and for me it was a very painful shock. A few months later in an attempt to overcome the mourning I went in psychoanalysis. At the end of this long and psychologically tiring journey, I thought I had overcome the trauma and, as far as possible, returned back to normality. I was wrong!